Hermeneutics and music criticism - Savage, Roger W. H. (Routledge, 2010)
Hermeneutics and Music Criticism forges new perspectives on aesthetics, politics and contemporary interpretive strategies. By advancing new insights into the roles judgment and imagination play both in our experiences of music and its critical interpretation, this book reevaluates our current understandings of music's transformative power. The engagement with critical musicologists and philosophers, including Adorno, Gadamer, and Ricoeur, provides a nuanced analysis of the crucial issues affecting the theory and practice of music criticism. By challenging musical hermeneutics? deployment as a.